Effective leadership: Competing Values Framework - Melo, Rosa Cândida de Carvalho Pereira de (2014)
Introduction: The importance of leadership in the performance of the organization has been demonstrated in various studies(1,2,3). Given that an effective leadership relies on the performance of leadership roles, it becomes essential to identify the led nurses' perceptions of the performance of leadership roles by the head nurse. Material and methods: A descriptive and correlational study was developed using Quinn's Model of Leadership, which is composed of 32 questions assessing leadership skills in 8 roles (mentor, facilitator, broker, innovator, monitor, coordinator, director and producer). The sample was composed of 690 nurses, mostly female (76.7%), with a mean age of 34.56 years and 12 years of professional experience. This instrument showed satisfactory psychometric properties. Results: The subordinate nurses' leadership perceptions showed mean scores above the midpoint of the scale in all leadership roles, with a mean and standard deviation of 5.00ï±1.15, respectively. Conclusions: The subordinate nurses' perceptions of a high level of performance of leadership roles indicate that these leaders are competent. A poor performance of the facilitator role suggests the need for head nurses to acquire leadership skills which help them manage interpersonal conflicts and promote cohesion and teamwork within the current context of health care restructuring and decreased nurse staffing levels.